Prévalence de HTLV-I au Bénin - DUMAS, M; Houinato, Dismand; ZOHOUN, K. THÉOPHILE; JOSSE, ROGER GÉRARD; DENIS, F; Verdier, M. (My University, 1989)
Poster présenté à la "IVème Conférence Internationale sur le Sida et Cancers associés en Afrique"